Hygiene Sanitasi dan Kualitas Mikrobiologi pada Depot Air Minum Isi Ulang di Wilayah Kerja Puskesmas Indralaya - Sevtariansyah Sevtariansyah; Intan Kumalasari; Sukarjo Sukarjo (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2025)
Refill Drinking Water Depots (DAMIU) are businesses that provide ready-to-drink drinking water through raw water processing using simple and modern technology. The existence of DAMIU is very important in meeting the community's need for drinking water, but aspects of sanitation hygiene and water quality must remain a primary concern to avoid health risks. This study aims to describe the sanitation hygiene conditions and assess the microbiological quality of refill drinking water at DAMIU in the Indralaya Community Health Center working area in 2025. The study used a descriptive method with a laboratory approach to 27 refill drinking water depots. Data were collected through observations of location conditions, buildings, equipment, and handler hygiene, and laboratory examinations were conducted on raw water and processed water samples. The results showed that the majority of depots (92%) had met the requirements related to location and buildings, while all depots (100%) met the standards for processing equipment. However, drinking water handlers still did not comply with applicable hygiene standards (100%). Only 70% of depots had suitable raw water sources, with 55% using the Sukomoro source, 41% using drilled wells, and 4% using the Dewa Air Prabumulih source. Laboratory tests found that two depots (8%) had raw water that tested positive for Escherichia coli, but all treated water samples met established microbiological standards. Overall, this study concluded that the location, building, and equipment of the Drinking Water Supply Unit (DAMIU) in the Indralaya Community Health Center (Puskesmas) area were satisfactory, but handler hygiene remained a weakness that needed immediate improvement. Furthermore, the physical and chemical quality of the water still required attention, although the microbiological quality met standards.